Women in Sport Coaching: Challenges, Stress and Wellbeing - Carson, Fraser; McCormack, Clara; Walsh, Julia (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
With a lack of women in leadership positions in sport, there are limited role models for women pursuing coaching careers and a number of traditional gender ideologies to overcome. Female coaches therefore face unique challenges, which can be vastly different to their male counterparts. This integrative review focused on the challenges that women face in the coaching domain and the impact that these can have on their well-being. Only four articles focused solely on female coaches since 2000. Despite the lack of literature several key themes have been identified. The main stressors relate to work-life balance, prolonged periods away from family, and a need to prove they are better than male coaches. Coping strategies focused on proactive anticipation and planning, and communication with others. There is also a lack of support for female coaches and inadequate salary to assist continued engagement. Developing female coaches through mentoring and gender specific coach education programs may counteract these issues.